ANALISIS POLA KONSUMSI KARKAS BEKU BROILER OLEH RUMAH TANGGA DI KOTA MEDAN - Muhammad Qori; Kurniawan Sinaga (Journal of Innovation Research and Knowledge, 2025)
his research aims to find out, analyze and present the consumption patterns of frozen broiler carcasses by households in the city of Medan, where this research was conducted on 100 respondents using Google Form and carried out through direct observation and interviews with respondents who are consumers of frozen broiler carcasses in the city of Medan with accuracy. data of 33.3% in each place, namely large malls, small stores and fresh markets. The results of research on Google Formshow that the majority of respondents do not look for information before making a purchase by 60% - 98%, apart from thatthe price of broiler carcasses in the product strategy research sub focus shows that respondents' purchases are influenced by price, credibility and availability with a percentage of 60% - 90%. And purchasing decisions are influenced by promotional strategies and distribution strategies with a percentage level of 70% -90%. Then, with direct observation and interviews with an assessment of the research attributes, the results showed different percentages in the categories of income, age, gender and education on consumption pattern parameters. In terms of price parameters, observations were made with the results that there was a decrease of 3.57% and a price increase of 5.45% for frozen carcasses and a significant increase in fresh carcasses at a rate of 3.57%-10.34% every week. The purchasing decision parameters of the proposed categories provide different percentages based on the mindset of the respondent in question. This research is able to provide information related to the development and marketing of frozen broiler carcasses.